EFEKTIFITAS KINERJA DOUBLE SKIN FASADE-GREEN WALL TERHADAP EFISIENSI ENERGI PENDINGINAN BANGUNAN - Cynthia Permata Dewi; Anang Bakhtiar (RUAS (Review of Urbanism and Architectural Studies), 2017)
Passive cooling strategy has been considered to apply due to its effectiveness. Double skin façade strategy is one of advance building façade technology in passive design. Moreover, Double skin façade-green wall is the development of conventional Double skin façade. The aim of this study is to observe and compare the performance of DSF and DSF-GW in reducing cooling energy. B-block building in Islamic University of Malang has been selected as case study. DesignBuilder-EnergyPlus was used as simulation tool in this study. The strategy of DSF and DSF-GW has been applied in along side of the building. The results show that the DSF-GW resulted best in reducing cooling energy demand up to 45% compare to conventional DSF.